2010
DOI: 10.3797/scipharm.1004-21
|View full text |Cite
|
Sign up to set email alerts
|

Production, Quality Control and Pharmacokinetic Studies of 166Ho-EDTMP for Therapeutic Applications

Abstract: 166Ho-EDTMP is a major therapeutic agent which is widely used in bone palliation therapy. In this study, a 166Ho-EDTMP complex was prepared successfully using an in-house synthesized EDTMP ligand and 166HoCl3. Ho-166 chloride was obtained by thermal neutron irradiation (1 × 1013 ncm−2s−1) of natural Ho(NO3)3 samples (specific activity = 3–5 GBq/mg), dissolved in acidic media. The radiochemical purity of 166Ho-EDTMP was checked by ITLC (>99%) and stability studies in presence of human serum and final preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…As a comparable 166 Ho bone pain palliation agent, 166 Ho-EDTMP has been proposed as a potential clinically used radiopharmaceutical by different groups [7,10]. A low liver uptake has been reported for 166 Ho-EDTMP which is considered a disadvantage as a bone pain palliative agent leading to less unwanted liver dose in patients (Fig.…”
Section: Biodistribution Of 166 Ho Cation and 166 Ho-pmd In Wild-typementioning
confidence: 98%
See 1 more Smart Citation
“…As a comparable 166 Ho bone pain palliation agent, 166 Ho-EDTMP has been proposed as a potential clinically used radiopharmaceutical by different groups [7,10]. A low liver uptake has been reported for 166 Ho-EDTMP which is considered a disadvantage as a bone pain palliative agent leading to less unwanted liver dose in patients (Fig.…”
Section: Biodistribution Of 166 Ho Cation and 166 Ho-pmd In Wild-typementioning
confidence: 98%
“…The use of bisphosphonates has made a significant change in the therapeutic approach to management of bone metastasis and pain prevention in breast cancer and multiple myeloma [4]. Various therapeutic 166 Ho bone-seeking agents have been reported such as 166 Ho-DOTMP [5,6], 166 Ho-EDTMP [7,8], 166 Ho-AP-DDMP [9], as well as 166 Dy/ 166 Ho-EDTMP demonstrating adequate properties as a stable in vivo generator system for bone marrow ablation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Total synthesis and production of 177 Lu-EDTMP were performed in the country and preclinical studies were reported in 2012. 61…”
Section: Local Clinical Evaluationsmentioning
confidence: 99%
“…Pre-clinical trials in dogs showed that 177 Lu-EDTMP is taken up almost exclusively by the skeletal system (>70%), with minimal activity accumulation in other organs (Bahrami-samani et al, 2012;Máthé et al, 2010;Saeed et al, 2012). Clinical trials with 177 Lu-EDTMP showed an obvious reduction in the pain scores at 2 to 6 weeks after the radiopharmaceutical administration.…”
Section: Iiig 177 Lu-ethylenediaminetetramethylene Phosphonic Acid mentioning
confidence: 99%